Chromosome-scale assembly of the Sparassis latifolia genome obtained using long-read and Hi-C sequencing. Issue 8 (22nd May 2021) - Yang, Chi; Ma, Lu; Xiao, Donglai; Liu, Xiaoyu; Jiang, Xiaoling; Ying, Zhenghe; Lin, Yanquan
Abstract: Sparassis latifolia is a valuable edible mushroom cultivated in China. In 2018, our research group reported an incomplete and low-quality genome of S. latifolia obtained by Illumina HiSeq 2500 sequencing. These limitations in the available genome have constrained genetic and genomic studies in this mushroom resource. Herein, an updated draft genome sequence of S. latifolia was generated by Oxford Nanopore sequencing and the high-through chromosome conformation capture (Hi-C) technique. A total of 8.24 Gb of Oxford Nanopore long reads representing ∼198.08X coverage of the S. latifolia genome were generated. Subsequently, a high-quality genome of 41.41 Mb, with scaffold and contig N50 sizes of 3.31 and 1.51 Mb, respectively, was assembled. Hi-C scaffolding of the genome resulted in 12 pseudochromosomes containing 93.56% of the bases in the assembled genome. Genome annotation further revealed that 17.47% of the genome was composed of repetitive sequences. In addition, 13, 103 protein-coding genes were predicted, among which 98.72% were functionally annotated. BUSCO assay results further revealed that there were 92.07% complete BUSCOs. The improved chromosome-scale assembly and genome features described here will aid further molecular elucidation of various traits, breeding of S. latifolia, and evolutionary studies with related taxa.